Padé method for the phase equation with singular potentials - Kloet, W. M.; Zimerman, A. H. (Springer Nature, 1970)
It is considered the possibility of applying Padé approximants for the phase equation with singular potentials. Some examples are considered which show that it is possible to obtain good results. © 1970 Società Italiana di Fisica.